Giant gastrointestinal stromal tumor of the proximal ileum - Kelen Christina A. Bezzerra (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT The gastrointestinal stromal tumors (GIST) are rare and consist in mesenchymal neoplasms of the gastrointestinal tract, which may affect any part of the gastrointestinal tract, and is more frequent in stomach. We report a case of a 65-years-old male patient who presented a mass in the proximal ileum found by exploratory laparotomy. The patient underwent a segmental enterectomy with total resection of the tumor and free surgical margins with the pathological diagnosis of GIST, confirmed by immunohistochemistry (CD117).